An Assessment of Critically Ill Children admitted to a General High Care Unit in a Regional Hospital in the Western Cape, South Africa - Vosloo, Ruan (Department of Paediatrics and Child Health, 2021)
Background Many critically ill children in South Africa are cared for in regional hospitals by general Paediatricians. Critically ill adults and children are usually cared for in the same units. There is limited data on the numbers of children admitted and the outcomes of these children. Objective To describe the patient profile and outcomes of children admitted to a general high care unit (HCU) in a regional hospital in the Western Cape, South Africa. Methods This was a retrospective descriptive study of all children admitted to the HCU of George Regional Hospital during a one year period (2016). Demographic data, HIV, anthropometric data, immunisation status, diagnoses, medical interventions, length of stay, death or survival, and referral data to the tertiary paediatric intensive care unit (PICU) were collected. The PIM3 score and Standardized Mortality Ratio (SMR) was calculated. Results Thirty percent (144/468) of the HCU admissions were children. Most (70%) were admitted after hours. Half were under 9 months (range 3 days to 149 months). Sixty-five percent of the children required respiratory support and 45% needed inotropic support. Twenty percent of the children were transferred to the PICU. Twelve children (8,5%) died with most deaths (75%) occurring at regional level. Half of the deaths were due to sepsis with pneumonia (25%) and diarrhoea with shock (25%) accounting for the rest. The cumulative PIM3 score was 9.049 (95%CI 6.430-11.668) with an SMR of 1.326 (95%CI 1.028-1.866) observed. Conclusion Critically ill children accounted for a third of HCU admissions. Most children needed medical interventions. These require specific training and equipment that are often lacking. After hours admissions also put strain on limited staff. Most children were successfully discharged demonstrating a good outcome. This was achievable with good channels of communication and transport to a tertiary PICU.